Potential of Hibiscus sabdariffa L. Calyx (Rosella) extract as antibacterial agent in dental disease: Phytochemical and chemical components profiling - Dewi Fatma Suniarti; Trijani Suwandi; Salsabila Aqila Putri; Dikdik Kurnia (Wolters Kluwer Medknow Publications, 2022)
Chemical characteristics of natural products are influenced by different external factors, varying according to the geographic origin. The ethanol extract of Hibiscus sabdariffa L calyx Indonesia has been studied in vivo and in vitro provide potential effect for dental field uses. Ethanol extract showed antibacterial to Streptococcus sanguinis as an inducer gingivitis, had an effect on the treatment of oral mucosa ulceration, and could inhibit the development of alveolar bone destruction. This study aims to determine the chemical groups and components of ethanol extract of H. sabdariffa L. calyces (Indonesia origin). Chemical group of ethanol extract H. sabdariffa L calyx Indonesia was analysis through phytochemical screening, whereas chemical components were detected through gas chromatography-mass spectrometry analysis. Saponins, tannins, phenolic, flavonoids, triterpenoids and glycosides, and 17 chemical components were identified in the ethanol extract of H. sabdariffa L calyx Indonesia. Among the chemical components, fatty acids group showed the most dominant. For standardization and develop of oral drug preparation, a better chemical components and phytochemical profiling are essential because the extract quality of herbs has various quality.